PELATIHAN MICROSOFT OFFICE SEBAGAI MODAL USAHA JASA PENGETIKAN DI PANTI ASUHAN AL-KAAF JABUNG KABUPATEN MALANG - Herman Hariyadi Ari Murtono; Fitri Fitri; Leonardo Kamajaya; Donny Radianto (Publisher UPT P2M Politeknik Negeri Malang, 2020)
Microsoft office training in an orphanage is very beneficial both for the students of the orphanage and the administrators of the orphanage. Knowledge of Microsoft Office can be used as a basic asset for typing services at the orphanage so that it can increase income for the orphanage. Al-Kaaf Orphanage, which is located in Jabung, Malang Regency, wants to open a typing service business but is still constrained by the lack of knowledge about basic Microsoft Office. In this service activity, Microsoft Office training will be given at the Al-Kaaf Orphanage. Students of the Al-Kaaf Orphanage will be introduced to MS.Office namely Word, Excel, and Power Point. With this application from MS.Office, it will increase knowledge for students of the Al-Kaaf Orphanage, so that it can be used as the basis for opening a typing service business.